2011
DOI: 10.1158/1535-7163.mct-11-0278
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PARP-1 by Olaparib (AZD2281) Increases the Radiosensitivity of a Lung Tumor Xenograft

Abstract: PARP-1 is a critical enzyme in the repair of DNA strand breaks. Inhibition of PARP-1 increases the effectiveness of radiation in killing tumor cells. However, although the mechanism(s) are well understood for these radiosensitizing effects in vitro, the underlying mechanism(s) in vivo are less clear. Nicotinamide, a drug structurally related to the first generation PARP-1 inhibitor, 3-aminobenzamide, reduces tumor hypoxia by preventing transient cessations in tumor blood flow, thus improving tumor oxygenation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(139 citation statements)
references
References 43 publications
8
128
0
Order By: Relevance
“…PARP1, the best-understood member of this family, facilitates base excision repair (2) and mediates important alternative DNA repair pathways (3). Preclinical studies identified PARP-mediated DNA repair as an essential survival mechanism for breast and ovarian cancers harboring BRCA1 or BRCA2 mutations deleterious to the homologous recombination DNA repair pathway (4,5). Thus, PARP inhibition in these cancers results in massive genomic instability that leads to cell death by synthetic lethality (6,7).…”
Section: Molecular Imaging: Pet Of Poly (Adp-ribose)polymerase Activimentioning
confidence: 99%
“…PARP1, the best-understood member of this family, facilitates base excision repair (2) and mediates important alternative DNA repair pathways (3). Preclinical studies identified PARP-mediated DNA repair as an essential survival mechanism for breast and ovarian cancers harboring BRCA1 or BRCA2 mutations deleterious to the homologous recombination DNA repair pathway (4,5). Thus, PARP inhibition in these cancers results in massive genomic instability that leads to cell death by synthetic lethality (6,7).…”
Section: Molecular Imaging: Pet Of Poly (Adp-ribose)polymerase Activimentioning
confidence: 99%
“…[21][22][23][24][25][26][27] In vivo, PARP inhibitors enhance radiation therapy in syngeneic and xenograft models for colon, lung, head and neck, and cervical cancers. 21,[28][29][30][31][32] Olaparib (AZD2281), which targets PARP1 and PARP2, is currently in several phase I and phase II trials for solid tumors as a single agent or in combination with chemotherapy and/or radiotherapy. 33 A phase I study is ongoing for olaparib plus temozolomide in patients with relapsed GBM (http://www.…”
mentioning
confidence: 99%
“…Immunohistochemical analysis of tumour sections after combined treatment revealed an increased number of apoptotic cells and a decrease in proliferating cells [84,87]. As previously described for nicotinamide and other benzamide analogs [92], PARP inhibitors can induce temporary vasodilation increasing perfusion of tumour blood vessels [82,85]. This vascular side effect of PARP inhibitors treatment enhances drug delivery (e.g.…”
Section: In Vivo Radiation Sensitivity After Parp Inhibition: Additiomentioning
confidence: 70%
“…A number of PARP inhibitors (ABT-888/Veliparib, AZD-2281/Olaparib, AG014699/ Rucaparib, MK-4827/Niraparib, AG14361, GPI-15427, E7016) have been shown to enhance tumour sensitivity to radiation in syngeneic and xenograft models of breast [79,80], colon [81][82][83], lung [79,84,85], nasopharyngeal [86], head and neck [87], and brain tumours [88][89][90][91] (Table 11.1). PARP inhibition combined with Colon carcinoma (SW620, LoVo) AG14361, i.p., 30 min before X-rays (5 or ionising radiation resulted in delayed tumour growth and extended median survival time.…”
Section: In Vivo Radiation Sensitivity After Parp Inhibition: Additiomentioning
confidence: 99%